2022
DOI: 10.3389/fphar.2022.916876
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Enhances the Anti-Cancer Effects of Cis-Platinum on Human Cervical Cancer Cell Lines by Activating the SIRT3 Relative Anti-Oxidative Pathway

Abstract: Background: Cervical cancer exerts considerable mortality in the world. The combinations of chemotherapy with cis-platinum were the first-line treatment in late-stage cervical cancer but may cause severe adverse effects. Resveratrol (RES, 3,5,4′-trihydroxy-trans-stilbene) is a phytoalexin, and it showed anti-cancer effects but with low toxicity and side effects. Herein, we examined the anti-cancer effects of cis-platinum combined with RES in human cervical cancer cell lines.Methods: The antiproliferative effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…In the present study, we examined cell fate decisions in the RES-treated A549 and H1299 lung cancer cell lines. Consistent with previous findings (Bian et al, 2022;Jiang et al, 2022;, RES reduced lung cancer cell viability, inhibited cell proliferation, and promoted cell senescence and apoptosis. Our results further showed that RES-induced ROS production by inhibiting Nrf2 expression in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we examined cell fate decisions in the RES-treated A549 and H1299 lung cancer cell lines. Consistent with previous findings (Bian et al, 2022;Jiang et al, 2022;, RES reduced lung cancer cell viability, inhibited cell proliferation, and promoted cell senescence and apoptosis. Our results further showed that RES-induced ROS production by inhibiting Nrf2 expression in a dose-and time-dependent manner.…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have confirmed that RES has antitumor potential in vitro and in vivo (Fu et al, 2021; Ko et al, 2017; Yousef et al, 2017). The anticancer effects and the underlying mechanisms of RES, such as cell proliferation inhibition (Qin et al, 2022), apoptosis induction (Jang et al, 2019), modulation of the immune system (Q. Zhang et al, 2020), and elevation effects of other anticancer drugs (Jiang et al, 2022) have been studied. However, the mechanism of action of RES remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“… Muhanmode et al (2022) showed that RES and curcumin reversed OC-acquired CDDP resistance in vitro by significantly inhibiting the PI3K/AKT/mTOR axis. Jiang et al (2022) demonstrated that RES treatment significantly enhances the sensitivity of SiHa cells to CDDP by activating SIRT3. Specifically, combination treatment increases the levels of hydrogen peroxide (H2O2) and manganese superoxide dismutase (MnSOD) in the cells and significantly reduces mitochondrial membrane potential (ΔΨm) and ROS levels.…”
Section: Combined With Antitumor Drugs Res Increases Efficacy and Red...mentioning
confidence: 98%
“…An NAD + -dependent deacetylase called Sirt3 participates in mitochondrial metabolic processes, including energy generation [6], the tricarboxylic acid cycle [7], and oxidative stress [8]. It has the functions of antioxidative stress [9], antiapoptosis [10], and the maintenance of metabolic homeostasis [11]. The primary source of the energy supply for the brain is the decomposition of glucose, which generates ATP.…”
Section: Introductionmentioning
confidence: 99%